PENINGKATAN KEMAMPUAN GURU DALAM MENGEMBANGKAN RPP BERBASIS DISCOVERY LEARNING MELALUI WORKSHOP DI UPT SD NEGERI RESAPOMBO 03 - Suharti; Isna Nurul Inayati (EBTIDA': Jurnal Pendidikan Dasar Islam, 2022)
Observations at SD Negeri Resapombo 03 show that some teachers at SD Negeri Resapombo are not used to applying and have not been able to develop lesson plans based on discovery learning. To address this, the researchers plan to carry out school action research with the theme of teacher competence in developing lesson plans based on discovery learning. This type of research is school action research. This research was conducted at Resapombo 03 Public Elementary School in November 2021 with the research subjects being all Resapombo Public Elementary School teachers. The technique of collecting data from this school action research is through qualitative data obtained from observation/observations, interviews and document studies. This procedure includes the following stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. Based on the results of reflection, monitoring and evaluation that have been carried out, it can be concluded that cycle 1 and cycle 2 activities have increased so that all objectives of the school action research activities are declared successful.